Constructing knowledges : the politics of theory-building and pedagogy in composition - Dobrin, Sidney I., 1967- (State University of New York Press, 1997)
Annotation An eloquent exploration of the academic debates over the value of theoretical and practical knowledges, discussions which are swimming like sharks around composition instructors. Dobrin (English, U. of Kansas) takes a practical stance, arguing that theory and practice must inform one another, laying out postmodern thought, postprocess theory, feminism and pedagogy, and radical pedagogy in a comprehensible manner so that they can actually affect the realities of classroom instruction. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: English language -- Rhetoric -- Study and teaching.; English language -- Composition and exercises -- Study and teaching.; Report writing -- Study and teaching.; Rapports -- Rédaction -- Étude et enseignement.; LANGUAGE ARTS & DISCIPLINES -- Rhetoric.; REFERENCE -- Writing Skills.; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing.; English language -- Composition and exercises -- Study and teaching; English language -- Rhetoric -- Study and teaching; Report writing -- Study and teaching; English.; Languages & Literatures.; English Language.